2012
DOI: 10.1186/1756-9966-31-28
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of hypoxia inducible factor-1α by cobalt chloride correlates with proliferation and apoptosis in PC-2 cells

Abstract: BackgroundThe exact mechanism of the effects of hypoxia on the proliferation and apoptosis in carcinoma cells is still conflicting. This study investigated the variation of hypoxia-inducible factor-1α(HIF-1α) expression and the apoptosis effect of hypoxia stimulated by cobalt chloride (CoCl2) in pancreatic cancer PC-2 cells.MethodsPC-2 cells were cultured with different concentration (50-200 μmol/L) of CoCl2 after 24-120 hours to simulate hypoxia in vitro. The proliferation of PC-2 cells was examined by MTT as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 25 publications
5
82
0
1
Order By: Relevance
“…In the case of a genetic over-stabilization of HiF-1, which is the case for various type of cancers [13,8], the increased ability of cancer cells to enter into a quiescent state is well described by our model. Indeed, this case can be modeled by multiplying [H 0 ] by an ǫ > 1 parameter to artificially increase the HiF-1 level.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the case of a genetic over-stabilization of HiF-1, which is the case for various type of cancers [13,8], the increased ability of cancer cells to enter into a quiescent state is well described by our model. Indeed, this case can be modeled by multiplying [H 0 ] by an ǫ > 1 parameter to artificially increase the HiF-1 level.…”
Section: Discussionmentioning
confidence: 73%
“…In other cases, genetic mutations induce an over-stabilization of HiF-1. It is the case for the renal clear carcinoma [13]. As a consequence, for the same oxygen pressure, HiF-1 will have a higher level in cancer cells than in normal cells [15].…”
mentioning
confidence: 94%
“…The effects of chemically induced hypoxia can be achieved by treating cells with deferoxamine (Guo et al, 2006) or dimethyloxalylglycine (Elvidge et al, 2006). Here, hypoxia was induced using a hypoxia chamber or CoCl 2 (Dai et al, 2012). Previous studies have reported that these methods have a similar effect on cells in creating a low-oxygen environment.…”
Section: Discussionmentioning
confidence: 99%
“…Der effektivste Zellverlust wurde in ei nem Kobaltchlorid (CoCl 2 )-Degene rations modell erreicht. Hier bei wird in der Zelle chemisch eine Hypoxie induziert [10]. …”
Section: Startschuss Fürunclassified